Urinary biomarkers of early renal injury in antiretroviral‐naïve HIV‐positive persons in Shanghai, China: comparison with the general population. Issue 8 (10th June 2021) - Le, XQ; Liu, DP; Chen, J; Gong, ZY; Xun, JN; Wang, JR; Sun, JJ; Steinhart, C; Liu, L; Shen, YZ; Qi, TK; Wang, ZY; et al.
Abstract : Objectives: People living with HIV (PLWH) have a high risk of kidney injury. Measurement of serum creatinine, along with proteinuria, is not sensitive to detect early kidney injury. Here, we investigated novel urinary biomarkers of early renal injury in PLWH. Methods: We performed a cross‐sectional study of 166 antiretroviral‐naïve PLWH and 99 HIV‐negative persons who all had an estimated glomerular filtration rate > 90 mL/min/1.73 m 2 . We compared the levels of seven urinary biomarkers between the two groups using the propensity score matching (PSM) approach and explored the risk factors associated with elevated urinary biomarkers in PLWH. Results: Eighty‐three pairs were successfully matched based on PSM. Compared with the HIV‐negative group, the HIV‐positive group had higher ratios of N‐acetyl‐β‐D‐glucosaminidase (NAG) to urine creatinine (UCr), alpha1‐microglobulin (α1‐M) to UCr, kidney injury marker‐1 (KIM‐1) to UCr, neutrophil gelatinase‐associated lipocalin to UCr, and epidermal growth factor to UCr, whereas the Tamm–Horsfall protein to UCr ratio and the abnormal albumin to UCr ratio were not significantly different. Positive correlations were observed between HIV RNA level and NAG: UCr ( rs = 0.32; P < 0.001) and α1‐M:UCr ( rs = 0.24; P = 0.002) ratios, and negative correlations were observed between CD4 cell count and NAG:UCr ( rs = –0.34; P < 0.001), KIM‐1:UCr ( rs = –0.16; P = 0.042) and α1‐M:UCr ( rs = –0.36; P < 0.001) ratios. In multivariate linear regression analyses, older age, lower total cholesterol and higher HIV RNA were independently associated with higher NAG:UCr; older age, lower total cholesterol and lower CD4 cell count were independently associated with higher α1‐M:UCr. Conclusions: In comparioson with HIV‐negative participants, PLWH were more likely to have tubular injury. Early antiretroviral treatment might mitigate the development of kidney injury.